Gardens of Vranyczany's manor houses in Hrvatsko Zagorje in the age of historicism - Obad-Šćitaroci, Mladen; Bojanić Obad Šćitaroci, Bojana; Ivkovčić, Zdenka (2021)
The Vranyczany-Dobrinović family (short: Vranyczany) is an aristocratic family that rose to power in Croatia in the second half of the 19th century. Members of the family possessed five manor houses surrounded by gardens with historicist features from the late 19th and early 20th century. All five are located in the hilly region of Hrvatsko Zagorje, which boasts the highest density of castles and manor houses in Croatia, built in continuity from the 17th until the beginning of the 20th century. The aim is to determine the features of the gardens of the explored castles, on the basis of photographs from the beginning of the 20th century as well as cartographic sources. A wealth of photographic documents from the beginning of the 20th century shows carefully landscaped and kept gardens and parks, with a full life flourishing in them. Vranyczany’s manor houses’ gardens are based on the Biedermeier and romantic tradition of garden culture. Towards the end of the 19th century, many gardeners trained in Vienna, Prague and other Central European cities, lived in Zagreb and the surrounding area. They passed down ideas related to the historicist garden culture and competed in artistic and horticultural gardening.
Bibliografske bilješke uz tekst ; bibliografija: 18 jed.
Summary.
Keywords: Vrtovi -- Kurije -- Historicizam; Obitelj Vranyczany-Dobrinović; Hrvatsko zagorje -- Oroslavje